أبعاد الشخصية الشعرية الأردية لميرزا غالب - مقدمة نقدية نفسية: The Dimensions of Mirza Ghalib’s Urdu Poetic Persona A Psycho-Critical Introduction - عبدالمجيب بسام; براء خالد هلال (Al Manhal Research Journal, 2024)
This research explores the psychological dimensions of the personality of the Indian poet Mirza Ghalib as reflected in his Urdu poetry, focusing on his inner contradictions, existential struggles, and the emotional and philosophical depth that characterizes his work. Ghalib emerges as a multi-layered poetic persona, intertwining self-reflection with profound existential questions about life and death, love and suffering, faith and doubt. He is not merely a poet who expresses his personal experiences; rather, he transforms his individual suffering into a universal human experience that resonates deeply with readers. The study also delves into the psychological aspect of Ghalib’s poetry through the lens of love, which he perceives as a supreme spiritual force, yet one perpetually laden with suffering, longing, and loss. This love manifests as a state of continuous burning. Furthermore, the research examines the philosophical dimension of Ghalib’s personality, where he articulates existential and mystical visions related to the relationship between man and God, and between the soul and matter.